2013
DOI: 10.4161/cbt.25093
|View full text |Cite
|
Sign up to set email alerts
|

“Selective cell death mediated by small conditional RNAs” is not selective

Abstract: Small conditional RNAs were used to kill cells selectively in a prior report. The method utilized the cellular innate immune response to dsRNA, causing PKR activation and cell death. We designed small conditional RNAs specific to a highly restricted transcript, that of the mesothelin gene expressed in various cancer lines and specific to a tpc/hpr fusion transcript expressed in a published "control" line. Hairpins of small conditional RNAs were functionally active in cell-free conditions. Hairpins were transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Extending the incubation time from 24 to 48 h resulted in higher cytotoxicity and selectivity, likely due to more advanced polymerization of oHP­(7) (Figure S9). Patel and Kern reported that RNA-HCR triggered by mutated mRNA as a cancer marker mediates cell death with no selectivity, probably because of nonspecific polymerization . Our results suggest that miRNA is a promising cancer biomarker to achieve selective cytotoxicity by RNA-HCR compared with mutated mRNA.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Extending the incubation time from 24 to 48 h resulted in higher cytotoxicity and selectivity, likely due to more advanced polymerization of oHP­(7) (Figure S9). Patel and Kern reported that RNA-HCR triggered by mutated mRNA as a cancer marker mediates cell death with no selectivity, probably because of nonspecific polymerization . Our results suggest that miRNA is a promising cancer biomarker to achieve selective cytotoxicity by RNA-HCR compared with mutated mRNA.…”
Section: Resultsmentioning
confidence: 69%
“…Patel and Kern reported that RNA-HCR triggered by mutated mRNA as a cancer marker mediates cell death with no selectivity, probably because of nonspecific polymerization. 29 Our results suggest that miRNA is a promising cancer biomarker to achieve selective cytotoxicity by RNA-HCR compared with mutated mRNA.…”
Section: ■ Resultsmentioning
confidence: 71%